Comparison between negative pressure wound therapy and platelet-rich plasma therapy in management of diabetic foot - Ekta Jain,; Saurabh Saxena,; Ajay Pathak,; Kusum Mahour,; Neha Sharma,; Shiv Shakti Yadav,; Rachna Gupta, (Asian Journal of Medical Sciences, 2024)
Background: Foot infections and ulceration are the most frequent reason for hospitalization in patients with diabetes mellitus (DM), accounting for up to 25% of all patients with DM admission. In the new advanced therapies for treating diabetic foot ulcers (DFUs), platelet-rich plasma (PRP) and negative pressure wound therapy (NPWT) have shown promising results. Aims and Objectives: The objectives of the study are as follows: To study the role of NPWT and PRP in management diabetic foot wounds and to compare granulation tissue formation, total duration of wound healing, and hospital stay between two therapies in diabetic foot wounds. Materials and Methods: This study was conducted with 100 patients of diabetic foot wounds meeting the inclusion criteria with pre-structured proforma and written informed consent for the therapies. After surgical debridement of the wound, the enrolled patients were randomized into two groups to receive either PRP therapy (Group A) (n=50) or NPWT (Group B) (n=50). Results: PRP and NPWT both were effective in healing process of diabetic foot patients. The mean value of Group A in granulation tissue score were 2.10±0.73 and 1.90±0.60 in Group B showed no significant difference. The duration of hospital stay was lower in Group A as compared to Group B that is 19.04±4.85 days in Group A and 35.86±7.35 days in Group B. The total duration of wound healing in Group A was longer that is 7.22±3.34 weeks in Group A and Group B was 4.0±2.27 weeks. Conclusion: PRP (Group A) and NPWT (Group B) are novel tools in management of DFUs. PRP is more simple, more safe, less costly, less equipment requirement, less complication, shorter time for the method, less painful, less hospital stay, and autologous nature in the preparation and had proved the superiority over NPWT.